The interactions between renewable portfolio standards and carbon emission trading in China: An evolutionary game theory perspective. (15th May 2023) - Hu, Yu; Chi, Yuanying; Zhou, Wenbing; Li, Jialin; Wang, Zhengzao; Yuan, Yongke
Abstract: Renewable Portfolio Standards (RPS) and Carbon Emission Trading (CET) are the policy instrument for China to achieve the low-carbon energy transition. Changes in policy combinations will affect the equilibrium state of the interactive system and bring uncertain risks to the expected effects of policy implementation. Given the assumption that the power users undertake RPS assessment and the CET market is extended to industries in addition to the power generation industry, this paper first constructs a game model in the context of RPS and CET where groups of power users and thermal power manufacturers jointly participate. Then, with China's provincial market data, it analyzed the evolution process of group strategy under different policy parameters and described the characteristics of the transition between the stable and unstable states of the system. Finally, a dynamic and differentiated mechanism design for policy parameters is proposed to restrain system oscillations. The simulation results reveal the interaction between market players' strategies, and a quantitative framework for analyzing system stability under different policy parameter combinations is proposed, which can provide an analysis framework for China to implement RPS and CET and deliver a relevant analysis basis for setting policy parameters. Highlights: Analyzing the interactive impact of RPS and CET markets on power users. Construct an evolutionary game framework. The process between stable and unstable states is characterized. Dynamic penalty mechanisms can make the system stable.